Conservation and propagation of Drosera schwackei: cryopreservation, in vitro germination, and development of an ornamental carnivorous species - Alves, Kamila Antunes; Costa, Dayvson Ayala; Titon, Miranda; Nery, Fernanda Carlota; Gonella, Paulo Minatell; Sousa, Tiago de Oliveira; Nery, Marcela Carlota (Ornamental Horticulture, 2025)
Drosera schwackei (Droseraceae) is a carnivorous species with high ornamental potential, but no established protocols exist for its cultivation and conservation. This study aimed to develop a protocol for in vitro germination, plant development, and cryopreservation of D. schwackei seeds. The experiment was conducted in a completely randomized design with a 2 x 4 factorial scheme (two concentrations of sodium hypochlorite and four immersion times), with four replications, each containing 30 seeds. The seeds were cultivated in different concentrations of MS medium (MS1/3, MS1/2, MS100%, and control with agar/water). Two experiments were carried out to evaluate the in vitro development of seedlings: 1) Testing different salt concentrations of MS medium (1/3, 1/2, and 100%); 2) MS1/3 medium supplemented with different concentrations of BAP (6-benzylaminopurine). For cryopreservation, seeds were stored in cryotubes and immersed in liquid nitrogen for 1, 6, 12, 24, 48, and 120 hours, with a control group inoculated on the same day. Disinfestation with 2% sodium hypochlorite for 10 minutes effectively stimulated germination. MS1/3 and MS1/2 media favored seed germination and seedling growth, while low concentrations of BAP promoted better plant development. The seeds survived cryopreservation for up to 120 hours in liquid nitrogen without impairing plant development or morphology. Sphagnum moss proved an efficient substrate for acclimating D. schwackei seedlings from in vitro cultivation.